Legal Aspects of Cross-Border Electronic Commerce Transactions with Quick Response Code (QR Code) Based Payments in the ASEAN Cooperation Framework - Yesi Ansari; Sunarmi; Detania Sukarja (Dinasti Research, 2024)
Cross-border e-commerce transactions, involving various payment methods such as international credit/debit cards, bank transfers, e-wallets, and QR Cross-border, have made it easier for consumers to engage in international transactions with varying costs. This study uses a qualitative descriptive approach with a literature study method and in-depth interviews. Data were obtained through document analysis related to QRIS policies, cross-border transaction reports, and interviews with experts in the field of e-commerce and digital law in ASEAN. The result although e-commerce offers significant benefits, legal challenges such as personal data protection, unclear legal status, and inter-country legal permissions still need to be addressed. In Indonesia, the QRIS standard launched by Bank Indonesia has helped improve the efficiency of the payment system and supports cross-border transactions in ASEAN, in line with regional economic integration through the ASEAN Economic Community (AEC). With Indonesia serving as the chair of ASEAN in 2023, collaboration in e-commerce and MSMEs continues to be strengthened, despite facing policy challenges, infrastructure, and cybersecurity concerns.